Analysis of Problem-Solving Ability of MTs Students In Solving Geometry Transformation Problems Through Online Learning - Lutfiani Cahyaningrum; Trisna Roy Pradipta (Universitas Negeri Makassar, 2021)
The research purpose to describe and analyze the mathematical problem solving abilities of MTs students in solving Geometry Transformation problems through Online Learning due to the Covid-19 pandemic int Indonesia. The research method used is descriptive qualitative. The subjects of this research were 3 students of MTs Al-Hamid Class IX who were selected as representatives of the very good problem-solving ability category, the problem-solving ability level category was sufficient, and the problem-solving ability level category was lacking. The data collection technique used was a test consisting of 4 non-routine items and interviews. The results of the analysis can be obtained: (1) students with excellent problem-solving abilities are able to fulfill the 4 steps of solving according to their pattern but there are errors in understanding the problem in question 1. (2) students with sufficient problem-solving skills are only able to solve problems in question 1 and 2 while 3 and 4 there are errors in understanding the questions. (3) students with poor problem solving skills were only able to solve problems in question 2, while in questions 3,4 and 5 there were errors in understanding the questions. The student error factor is due to the lack of understanding of the concept of geometric transformation to do the test because the geometric transformation test questions given are non-routine, while the geometric transformations that are often encountered only substitute formulas without understanding the concept of geometric transformation which includes translation, reflection, rotation and dilation. Many have to do with everyday life so that students experience difficulties in what is meant in the questions, especially in questions 3 and 4.